Karakterisasi dan Penetapan Kadar Flavonoid Total Ekstrak dan Fraksi Bunga Pepaya Jantan (Carica papaya L.) dengan Spektrofotometri UV-Vis - Dilla Nur Pratiwi; Nastiti Utami; Diah Pratimasari (Jurnal Ilmiah Farmasi, 2022)
Background: The potential of pepaya jantan flowers (Carica papaya L.) as functional herbal ingredients, such as antioxidants, is influenced by the activity of secondary metabolites, one of which is flavonoids. Objective: This study aims to determine the total flavonoid content and characterization of flavonoids in the ethanol extract and flower fraction of papaya jantan (Carica papaya L.). Method: Pepaya jantan flower was extracted by maceration using ethanol 70% then fractionated using multilevel fractionation. The identification of flavonoids was tested using Taubeck, Wilstater, and TLC. Extract and fractions were determined of flavonoid content using the colorimetric method and identification of flavonoids based on the wavelength of cinnamoyl and benzoyl in the spectrum UV-Vis. Results: The results of the determination of flavonoid content showed that ethanol extract was the highest at 0.6805 ± 0.0045 %QE and n-hexane fractions were the lowest at 0.4178 ± 0.0058 %QE. Identification of flavonoids using the UV-Vis spectroscopy method showed the absorption of substituted 3-OH flavonol and free 3-OH flavonol.  Conclusion: The highest flavonoid content was found in the ethanol extract of papaya jantan flower. The types of flavonoids in the extract and fractions of male papaya flower indicated the type of flavonol based on the wavelength of cinnamoyl and benzoyl.